2021
DOI: 10.1242/jcs.254979
|View full text |Cite
|
Sign up to set email alerts
|

An SNX10-dependent mechanism downregulates fusion between mature osteoclasts

Abstract: Homozygosity for the R51Q mutation in sorting nexin 10 (SNX10) inactivates osteoclasts (OCLs) and induces autosomal recessive osteopetrosis in humans and in mice. We show here that fusion of wild-type murine monocytes to form OCLs is highly regulated, and that its extent is limited by blocking fusion between mature OCLs. In contrast, monocytes from homozygous R51Q SNX10 mice fuse uncontrollably, forming giant dysfunctional OCLs that can become 10-100 fold larger than their wild-type counterparts. Furthermore, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 57 publications
(84 reference statements)
1
16
0
Order By: Relevance
“…prominent in late endosomes (Haucke, 2005;Wallroth and Haucke, 2018;Barnea-Zohar et al, 2021). In agreement with these findings, studies in RAW264.7 cells indicated that SNX10 binds the lipid kinase PIKfyve, which phosphorylates PI3P into PI(3,5)2P, and both PIKfyve and SNX10 co-fractionate in these cells together with EEA1, a marker of early endosomes (Battaglino et al, 2019;Sultana et al, 2020).…”
Section: Cell-based Studiessupporting
confidence: 71%
See 4 more Smart Citations
“…prominent in late endosomes (Haucke, 2005;Wallroth and Haucke, 2018;Barnea-Zohar et al, 2021). In agreement with these findings, studies in RAW264.7 cells indicated that SNX10 binds the lipid kinase PIKfyve, which phosphorylates PI3P into PI(3,5)2P, and both PIKfyve and SNX10 co-fractionate in these cells together with EEA1, a marker of early endosomes (Battaglino et al, 2019;Sultana et al, 2020).…”
Section: Cell-based Studiessupporting
confidence: 71%
“…OCLs from these mice lacked RBs and could not acidify the cell-bone interface, in agreement with their complete lack of activity in in vitro pit resorption assays. R51Q SNX10 OCLs also stained poorly for TRAP, appeared to be less adherent, and were noticeably more fragile and shorter-lived than their wild-type or heterozygous counterparts (Barnea-Zohar et al, 2021). Levels of CTX in circulation were elevated in these mice despite clear OCL inactivity (Stein et al, 2020), similar to the SNX10 KD mice (Ye et al, 2015).…”
Section: Mouse Models Of Snx10 Mutations In Aromentioning
confidence: 71%
See 3 more Smart Citations